PENGARUH KODE ETIK PROFESI AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT YANG DI HASILKAN AUDITOR PADA KAP YANG TERDAFTAR DI JAKARTA TIMUR - Adly Yustar Afif (2021)
This research is a quantitative study which aims to determine the effect of the code of ethics of the public accounting profession on the quality of audits produced by auditors at registered public accounting firms in East Jakarta. This study uses auditors who work at public accounting firms, especially those registered in East Jakarta, as a sample. Sample selection is carried out randomly after determining the number of samples that have been determined. Hypothesis testing in this study using Multiple Linear Regression Analysis with SPSS version 25 program. By using the t test and a significance level of 5% (0.05). The results of the test are obtained (1) there is a significant positive effect between the auditor's integrity variable on the resulting audit quality, (2) there is a positive significant effect of auditor objectivity on the resulting audit quality, (3) there is no significant influence between the auditor's competence and the audit quality. resulting, (4) there is no influence between the auditor's accountability variable on the resulting audit quality, (5) there is an influence between the independent variable on the quality of the audit produced.